Corpos estranhos no fígado e vias biliares de um suíno - Machado, A V; Rangel, N M (Revista Ceres, 2024)
The authors report a case of foreign in the gall bladder and biliary ducts (intra and extrahepatic) of a pregnant sow dead from hog-cholera. The foreign bodies consisted mainly of sand, mixed with corn kernels and small conglomerates of caseous. appearance, and weighted 700 grams. Besides this, they found two concretions, in the intra hepatic biliary ducts and some larvae of Stephanurus dentatus. Attention should be called to the excellent nutrition status of the sow, the absence of icterus, and the discrete hepatic lesions which consisted essencially of cirrotic areas around the biliary ducts with foreign bodies. The aa. discusse the mechanism of penetration of such foreign bodies in the biliary ducts and in this case, believe that the main factor was the abnormally large diameter of the cholecocus.